Digital Marketing Strategies and The Marketing Performance of Top 100 Small and Medium Enterprises (SMESs) in Kenya - Kalei, Anne (International Journal of Research in Management & Business Studies, 2020)
The purpose of this study was to investigate digital marketing strategies and the marketing performance of Top 100 SMEs in Kenya. The objective of this study was to establish the effectiveness of digital marketing strategies on the marketing performance of top 100 small and medium enterprises (SMEs) in Kenya. The study employed a regression design. The researcher developed a set of questionnaire for data collection from Top 100 SMEs and 100 SMEs constituted the target population for the study. Stratified random sampling technique was employed to thirty (30) Top 100 SMEs in the Commercial and Trade, Service, Construction and Technology sectors. The study was limited to the SMEs that were in the Top 100 list in 2016. The researcher issued questionnaires to the sampled SMEs and data was collected using the drop and pick method. Quantitative data was collected and analysed by use of regression analysis to establish the significance of correlation coefficient on the association between the variables. The study found that digital marketing strategies had a significant influence on the marketing performance of SMEs. The study concluded that the adoption of digital marketing strategies has a positive influence on the marketing performance of SMEs. It was recommended that SMEs adopt digital marketing strategies such as social media, search engine optimization, display adverts and websites and blogs. The study suggested that there was need for more studies to be conducted on the same subject on other SMEs and cadres of companies for comparative results.